From intention to action: Habits, feedback and optimizing energy consumption in South Korea. (June 2020) - Lee, Eungkyoon; Kang, Myounggu; Song, Jaemin; Kang, Myunghoon
Highlights: We develop a deductive model that explains how the intention-action gap leads to energy overconsumption. Improved feedback about energy consumption stimulates energy-saving behavior narrowing the intention-action gap. The positive effect of feedback is stronger for high energy users than for low users. Abstract: In energy research, debate continues as to the effects of habits and feedback on energy consumption. Particularly, habits have been considered as one of the primary causes of inefficient energy consumption, whilst feedback has been explored as a solution to mitigate the inefficiencies. However, relatively little effort has been put into investigating how and why feedback mitigate the inefficient energy consumption caused by habits. Here, to tackle this issue, we synthesize the two flows of research on habits and feedback and develop a deductive model that elucidates the links between individuals' cognitive states and actual consumption behavior. Our model explains how the intention-action gap leads to energy overconsumption and illustrates how feedback influences this. We test the empirical validity of our model in a field experimental setting. Our results imply that improved feedback helps reduce energy consumption by preventing consumers' misperceptions of their level of energy use, thereby narrowing their intention-action gap. We anticipate that our logic and findings will help develop methods of intervention for behavior change without coercive restraints on freedom of consumer choice.